Digital technology - great assistant to renovate higher education - Hoàng, Hòa Bình (2020)
General reasons for injury rale, its timely prevention and treatment are considered in this article. The authors makes three main factors to avoid injuries in choreagraphy process, also they focus attention on conrrect diagnostics of damages of damages and diseases of dancers on condition of knowledge of dancing activity's specifics